Islamo-English: an exposition - Mohamed Ali, Haja Mohideen (2012)
Islamo-English is a term coined by or preferred by the present researcher to refer to the use of Islam-related expressions in English usage. The mixing of English and Islam-related terms in both scholarly works and popular reading materials has bee in use for a long time. But these expressions have not been sufficiently researched, albeit some studies have been done. The aim of this paper is to present the mixing of English and Islam-related vocabulary in Arabic (and Malay and other Muslim-majority languages) in different fields using non-academic, non-scholarly reading materials and casually printed materials).